Фразеологічні номінації концепту міграція в англомовній картині світу - Левін, Олег Євгенович (Харківський національний університет імені В. Н. Каразіна, 2025)
The research is devoted to the analysis and interpretation of phraseological units that represent the concept of MIGRATION in the English language. A wide range of phraseological units, the semantics of which is related to this socially significant phenomenon, has been studied. Special attention has been paid to the linguistic features, the semantic nuances and the use of idioms. The results of the study indicate that idioms related to the concept of MIGRATION perform an important function in speech and communication, providing not only linguistic but also cultural context.
Keywords: concept; phraseological unit; linguistic worldview; migration; analysis; idiom